2012
DOI: 10.5455/gmj-30-2011-65
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and clinical progress of HIV-infected patients on highly active antiretroviral therapy in north west Ethiopia

Abstract: The survival benefits of highly active antiretroviral therapy (HAART) in HIV infected patients have been studied well in the developed world. In resource poor settings like Ethiopia such treatment was started only in 2003. As a result, the existing treatment guidelines and recommendations are based on data from the developed world. The objective of this study was to determine the immunological and clinical progress in HIV/AIDS patients in one year data review of patients' card who initiated on HAART in Ethiopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
1
3
0
Order By: Relevance
“…In about a quarter (22.7%) of PLWHA, chronic diarrhea was seen in Southern Ethiopia [ 16 ]. The cumulative incidence of recurrent OIs like recurrent upper respiratory tract infection, chronic diarrhea, bacterial pneumonia, oral candidiasis, herpes zoster, extra pulmonary tuberculosis, PCP, and pulmonary tuberculosis in current study was 17.1%, 14.8%, 9.8%, 9.8%, 9.3%, 9.3%, and 7%, 5.4%, respectively, and this finding is relatively in line with some figures of OIs in the studies [ 9 , 10 , 12 14 ] though it is lower than some other studies [ 11 , 15 , 16 ]. The possible reasons for discrepancy would be different in study design (the prior ones that are cross-sectional), study population (prior ones using PLWHA when coming to initiate ART which will increase the prevalence since ART is initiated using WHO stage of disease and CD4 count), study area, and other sociocultural practices.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In about a quarter (22.7%) of PLWHA, chronic diarrhea was seen in Southern Ethiopia [ 16 ]. The cumulative incidence of recurrent OIs like recurrent upper respiratory tract infection, chronic diarrhea, bacterial pneumonia, oral candidiasis, herpes zoster, extra pulmonary tuberculosis, PCP, and pulmonary tuberculosis in current study was 17.1%, 14.8%, 9.8%, 9.8%, 9.3%, 9.3%, and 7%, 5.4%, respectively, and this finding is relatively in line with some figures of OIs in the studies [ 9 , 10 , 12 14 ] though it is lower than some other studies [ 11 , 15 , 16 ]. The possible reasons for discrepancy would be different in study design (the prior ones that are cross-sectional), study population (prior ones using PLWHA when coming to initiate ART which will increase the prevalence since ART is initiated using WHO stage of disease and CD4 count), study area, and other sociocultural practices.…”
Section: Discussionsupporting
confidence: 88%
“…In Northwest Ethiopia, about 88.9% pre-ART HIV patients had OIs [ 10 ]. Another study in similar area also showed that 82.4% pre-ART HIV patients have OIs [ 11 ]. The respective prevalence of pulmonary tuberculosis and cryptococcal meningitis among PLWHA in North West Ethiopia was about 7.5% [ 14 ] and 8.3% [ 15 ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The correct use of antiretroviral (ARV) drugs significantly reduces viral load resulting in reduced morbidity and mortality among HIVinfected patients (Egger et al, 2002;Edwards et al, 2015). Studies have shown that prolonged viral suppression is associated with substantial increases in CD4 cell counts and reduction in the rates of opportunistic infections associated morbidity and mortality * Correspondence E-mail: benkidenya@yahoo.com (Battegay et al, 2006;Wabe & Alemu, 2012). Such immune recovery has been shown to be partial consisting of an initial rapid recovery of CD4 T lymphocytes as well as improvement in their function (García et al, 2004;Moore & Keruly, 2007;Zhou et al, 2010).…”
Section: Introductionmentioning
confidence: 99%